The Effectiveness of the Role of Adhoc Bodies in Handling Voter List Updating Problems in General Elections - Mohammad Naufal Maajid; Sri Sutjiatmi; Arif Zainudin (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to reveal the effectiveness of the Adhoc Agency's role in handling voter list updates in general elections, with a focus on Tegal Timur Subdistrict, Tegal City. Updating the voter list is a crucial stage in the conduct of elections as it determines the accuracy of voter data and the legitimacy of election results. The study employs Performance Prism analysis using the Nvivo software tool, based on transcripts of interviews with two commissioners and the Chair of the Election Commission (PPK). The research findings indicate that the Ad Hoc Body has a clear function, but its effectiveness is still hindered by several factors, including high population mobility, which leads to an increase in issues, low public participation in population administration, and the inadequate development of technology that should support the performance of election organisers. These findings occurred during the 2024 general and regional elections. Overall, these findings underscore that the challenges in updating the voter list are multidimensional. Administrative and technological barriers cannot be separated from participatory and structural aspects. Therefore, collaboration is needed between stakeholders of the Ad Hoc Agency and the government through a comprehensive and inclusive approach that not only focuses on updating the information system but also encourages active community involvement, whether through strengthening human resources or socialisation, and enhancing institutional capacity to ensure accuracy and fairness in the compilation of the voter list. Keywords: General Election; Ad Hoc Agency; Voter List Updates;